1992
DOI: 10.1038/355453a0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of members of the putative olfactory receptor gene family in mammalian germ cells

Abstract: A series of genomic and complementary DNA clones encoding new putative members of G protein-coupled receptors were isolated using homology cloning and low-stringency polymerase chain reaction. Among the unidentified receptors ('orphan receptors'), a human genomic clone (HGMP07) was characterized by the presence of its transcripts in the testis and by its belonging to a large subfamily of genes sharing extensive sequence similarities. Sequence comparison demonstrated that this gene subfamily is the human counte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
220
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(232 citation statements)
references
References 11 publications
11
220
0
1
Order By: Relevance
“…However, recent data indicate that several members of the olfactory receptor gene family are expressed in tissues unrelated to olfaction. Some of these ''putative ORs'' have been found to be expressed in taste buds (23,24), in germ cells (4,22), in the developing heart (25), and along the olfactory nerve (7,8). Herein, we report the transient expression of such a receptor in the notochord.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent data indicate that several members of the olfactory receptor gene family are expressed in tissues unrelated to olfaction. Some of these ''putative ORs'' have been found to be expressed in taste buds (23,24), in germ cells (4,22), in the developing heart (25), and along the olfactory nerve (7,8). Herein, we report the transient expression of such a receptor in the notochord.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding putative odorant receptors (ORs) have been recently characterized in several vertebrate species including mouse (1,2), rat (3), dog (4), fish (5,6), chicken (7,8), and human (4,9). The putative OR family belongs to the large multigene superfamily of seven-transmembrane-domain Gprotein-coupled receptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that each olfactory neuron expresses only one of the hundreds of functional OR genes (Chess et al 1994;Malnic et al 1999;Serizawa et al 2000), but this one neuron-one receptor hypothesis is still controversial (Mombaerts 2004a). OR genes are also expressed in testis, and it has been suggested that they mediate sperm chemotaxis (Parmentier et al 1992;Spehr et al 2003). ORs are G-protein coupled receptors (GPCRs) that contain seven transmembrane a-helical regions.…”
Section: Introductionmentioning
confidence: 99%
“…OR genes are expressed not only in the olfactory epithelium but also in numerous other organs (12)(13)(14)(15), suggestive of additional functions. In the testes of several mammalian species including man, at least 50 OR genes are transcribed that could be involved in sperm development, sperm competition, chemotaxis, or interaction between sperm and oocyte (16 -18).…”
mentioning
confidence: 99%